Durability Studies on High Strength Concrete (Pakistan Journal of Scientific Research, 2022)
High strength concrete (HSC) is very useful for recent construction technology; the major problem of HSC is the insufficient ductility. To investigate the ductility of HSC, the entire stress-strain curve, especially in the descending branch, shall be recorded. The aim of this study is to investigate the durability of High strength concrete for different replacement levels of mineral admixtures by alternate wetting and drying phenomenon which includes; acid attack, sulphate resistance and marine Environment and also to determine the compressive strength of concrete as GGBFS partial replacement for cement. Concrete mix is designed for M80 Grade of concrete using modified ACI method. Maximum Compressive Strength of 96.4MPa and 91.6 MPa at 28days were found for the HSC specimens at a partial replacement of cement with 30% of GGBFS in normal water curing and accelerated curing tank respectively. The specimens immersed in marine solution were found to have less weight loss when compared to acids and sulphate solution.
Keywords: High strength concrete; M80 Grade; Compressive strength; durability